2022
DOI: 10.3390/molecules27103260
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Toxicity of Bisphenols Together with UV Filters in Water: Identification of Synergy and Antagonism in Three-Component Mixtures

Abstract: Contaminants of emerging concern (CEC) localize in the biome in variable combinations of complex mixtures that are often environmentally persistent, bioaccumulate and biomagnify, prompting a need for extensive monitoring. Many cosmetics include UV filters that are listed as CECs, such as benzophenone derivatives (oxybenzone, OXYB), cinnamates (2-ethylhexyl 4-methoxycinnamate, EMC) and camphor derivatives (4-methylbenzylidene-camphor, 4MBC). Furthermore, in numerous water sources, these UV filters have been det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In general, so far little is known about the interactions of chemicals in mixtures. On the one hand, it is commonly found that mixed toxic chemicals result in synergistic or additive effects, however, on the other hand, there are also some pieces of evidence about antagonistic interactions between UV filters [ 102 104 ]. Based on the results presented in Table 3 it can be summarized that the calculated total TU value of 16 out of 20 binary and ternary mixtures was greater than 1, indicating that the toxicity of mixtures on Allivibrio fisheri was antagonistic.…”
Section: Discussionmentioning
confidence: 99%
“…In general, so far little is known about the interactions of chemicals in mixtures. On the one hand, it is commonly found that mixed toxic chemicals result in synergistic or additive effects, however, on the other hand, there are also some pieces of evidence about antagonistic interactions between UV filters [ 102 104 ]. Based on the results presented in Table 3 it can be summarized that the calculated total TU value of 16 out of 20 binary and ternary mixtures was greater than 1, indicating that the toxicity of mixtures on Allivibrio fisheri was antagonistic.…”
Section: Discussionmentioning
confidence: 99%
“…This can occur even if there are no obvious adverse effect levels (NOAELs) individually 43,44 . In a recent study where mixtures of BPs and UV‐filters were tested as a mixture, it was found that mixing any three BPs with 4‐MBC can lead to strong synergy effects 45 . The particular mixtures contained any pair of three BPs (e.g., BPA + BPS, BPA + BPF and BPS + BPF), together with one sunscreen component, that is, oxybenzone, OXYB, 4‐MBC or cinnamates (2‐ethylhexyl 4‐methoxycinnamate, EMC).…”
Section: Discussionmentioning
confidence: 99%
“…Mixtures of these contaminants may synergistically exert biological effects and no longer conform to the stoichiometric response curve [ 10 , 11 , 13 ]. The biological effects of chemicals or mixtures are difficult to assess using traditional toxicological methods [ 14 , 15 , 16 ]. We lack validated models and methods to study the damage from exposure to high numbers of chemicals and their mixtures in humans.…”
Section: Introductionmentioning
confidence: 99%